2010
DOI: 10.1016/j.tics.2010.09.001
|View full text |Cite
|
Sign up to set email alerts
|

The functional role of cross-frequency coupling

Abstract: Recent studies suggest that cross-frequency coupling (CFC) may serve a functional role in neuronal computation, communication, and learning. In particular, the strength of phase-amplitude CFC differs across brain areas in a task-relevant manner, changes quickly in response to sensory, motor, and cognitive events, and correlates with performance in learning tasks. Importantly, while high-frequency brain activity reflects local domains of cortical processing, low-frequency brain rhythms are dynamically entrained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

56
1,663
1
10

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,764 publications
(1,793 citation statements)
references
References 90 publications
56
1,663
1
10
Order By: Relevance
“…However, a less evident increase in the a band could be observed in some subjects and in some sensors. Then, we believe it is important also to study this band and its possible interaction with b and c as others have previously suggested (Canolty and Knight 2010). We strongly believe that the analysis framework here presented has the potential to help to understand the nature of such coupling at different stages of the learning process.…”
Section: Resultsmentioning
confidence: 65%
“…However, a less evident increase in the a band could be observed in some subjects and in some sensors. Then, we believe it is important also to study this band and its possible interaction with b and c as others have previously suggested (Canolty and Knight 2010). We strongly believe that the analysis framework here presented has the potential to help to understand the nature of such coupling at different stages of the learning process.…”
Section: Resultsmentioning
confidence: 65%
“…It has already been demonstrated that CFC and (particularly) PAC play an important role in the communication between regions that produce different brain rhythms (Palva et al, 2005;Canolty et al, 2010), and constitute the principle mechanism of how local oscillatory activity of low frequency is interacting with distant brain areas functioning at higher frequency (Florin et al, 2015). Results from recent studies in both animals and humans support a mechanism that oscillations at higher frequencies are often modulated by the phase of slower phase fluctuations (Osipova et al, 2008;Tort et al, 2008Tort et al, , 2009Tort et al, , 2010Cohen et al, 2009a, b;Colgin et al, 2009;Axmacher et al, 2010a, b;Voytek et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Recent data indicate that distinct frequencies are involved in different computations as well as coordination at varying spatial scales [18]. Moreover, interactions between different frequencies enlarge significantly the coding space through establishing coherence between different rhythms with important consequences for cognitive processes [19]. Much work has been devoted to the analysis of synaptic mechanisms and circuits that support the generation of oscillatory activity and its synchronization over short and long distances [20], respectively, which makes it possible to relate abnormalities of these dynamic phenomena to specific neuronal processes [21].…”
Section: Disconnection and Dysconnectivity In Schizophreniamentioning
confidence: 99%